2002
DOI: 10.1375/twin.5.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Speech in Same- and Different-sex Twins 4 and 5 Years Old

Abstract: The purpose of this study was to examine the impact of the sex makeup of pairs of twins on language acquisition. Past research indicated that this variable plays a role in speech problems of twin children. The questions raised were whether being a boy or a girl and having a boy or girl co-twin affected linguistic performance. A language test was given to 30 pairs of boy-girl twins, 16 pairs of boy twins, and 16 pairs of girl twins whose average age was 4 years 8 months. Their test scores confirmed our hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In contrast to previous research showing a female advantage among twin dyads in terms of speech production (Galsworthy et al, 2000; Rice et al, 2014), we did not find any evidence of differences either in speech or gesture production among twin dyads. However, even though the difference was not significant, it is worthy to note that both girl-girl and girl-boy twins tended to produce a greater amount, diversity, and complexity of speech compared to boy-boy twins, in line with the previous findings (Garitte et al, 2002; Gücüyener et al, 2011). This tendency was reversed for gesture production: boy-boy twins tended to use a greater amount and diversity of gestures compared to girl-girl and girl-boy twins.…”
Section: Differences Between Different Twin Dyadssupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast to previous research showing a female advantage among twin dyads in terms of speech production (Galsworthy et al, 2000; Rice et al, 2014), we did not find any evidence of differences either in speech or gesture production among twin dyads. However, even though the difference was not significant, it is worthy to note that both girl-girl and girl-boy twins tended to produce a greater amount, diversity, and complexity of speech compared to boy-boy twins, in line with the previous findings (Garitte et al, 2002; Gücüyener et al, 2011). This tendency was reversed for gesture production: boy-boy twins tended to use a greater amount and diversity of gestures compared to girl-girl and girl-boy twins.…”
Section: Differences Between Different Twin Dyadssupporting
confidence: 85%
“…Sex differences in early speech and gestures produced by twins Most of the earlier research on twins focused on same-sex twin dyads. Several of these studies investigated the effect of child sex on language development and showed that boy-boy twins lag behind girl-girl twins in their language abilities (Davis, 1937;Day, 1932;Galsworthy, Dionne, Dale & Plomin, 2000;Garitte, Almodovar, Benjamin & Canhao, 2002;Gücüyener et al, 2011;Hay & O'Brien, 1983;Rice et al, 2014). On average, boy-boy twins have been shown to be 6-to-8-months behind girl-girl twins in their expressive and receptive language skills, as assessed by parent report at age 2;6 (Hay & O'Brien, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 30 months of age, twin boys were 8 months behind in expressive language and 6 months behind in verbal comprehension (Hay et al, 1987) compared to girls. Similarly, when male twin pairs were compared with female or different-sex pair twins using a language test, it was noted that female and opposite-sex twin pairs performed better than male twin pairs (Garitte et al, 2002). The reason for this gender difference is unclear.…”
Section: Gender Comparisonmentioning
confidence: 99%